Measuring stability and degradability of agroforestry systems - Ferreira, Pedro; Kass, Donald Charles Lieber (International Center for Tropical Agriculture, 1995)
Tropical agriculture usually deals with severe limitations on management alternatives, arising from a combination of factors such as low-resource farmers, fragile lands, high pest susceptibility, etc. Under these conditions, agroecosystem properties other than productivity, such as stability, sustainability, degradability, etc. are of crucial importance. Although a conceptual framework has been elaborated on these topics, the problem of evaluating agroecological system properties and comparing systems is still an almost open field. In addition to evaluating system properties, an appraisal of the relative importance of factors which affect those properties should be given.